2017
DOI: 10.1097/ta.0000000000001590
|View full text |Cite
|
Sign up to set email alerts
|

Early heparin administration after traumatic brain injury

Abstract: Heparin after TBI reduces tissue LEU sequestration and edema in injured brain for up to 4 days. This is associated with persistent improved cognitive recovery, but only when low-dose UFH is given. Early administration of UFH following TBI may blunt LEU-related cerebral swelling and slow progression of secondary brain injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 35 publications
1
4
0
Order By: Relevance
“…Nagata et al has shown that early administration of heparin is associated with a significant decrease in post-TBI inflammation and preservation of cognitive outcomes. These results were further supported by prior studies investigating the role of low-molecular weight fractionated heparin, enoxaparin ( 2 , 23 , 33 35 ). Human studies investigated the role of enoxaparin (low-molecular weight fractionated heparin) in aneurysmal SAH with mixed results ( 36 , 37 ).…”
Section: Neuroprotective Effects Of Heparin In Subarachnoid Hemorrhagsupporting
confidence: 76%
See 2 more Smart Citations
“…Nagata et al has shown that early administration of heparin is associated with a significant decrease in post-TBI inflammation and preservation of cognitive outcomes. These results were further supported by prior studies investigating the role of low-molecular weight fractionated heparin, enoxaparin ( 2 , 23 , 33 35 ). Human studies investigated the role of enoxaparin (low-molecular weight fractionated heparin) in aneurysmal SAH with mixed results ( 36 , 37 ).…”
Section: Neuroprotective Effects Of Heparin In Subarachnoid Hemorrhagsupporting
confidence: 76%
“…The accepted mechanism of action of leukocyte extravasation is through interaction of cell glycoproteins with the selectin family of proteins, generally expressed on endothelial cells ( 22 ). Heparin has been shown to specifically decrease the number of leukocytes participating in the inflammatory response to any insult to the central nervous system ( 23 , 24 ).…”
Section: Profile: Characteristics and Mechanism Of Actionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, increased expression of chemokines and chemokine receptors following TBI, including CXCL2, CXCR2, CCL2, CXCR4, and chemokine-like factor 1 (CKLF1), has been shown to further permeabilize the BBB [ 261 264 ] and attract neutrophils [ 265 , 266 ]. This causes a significant influx of peripheral immune cells into the brain following TBI, which has been found to worsen edema and neuronal damage [ 267 269 ].…”
Section: Acute Damage To the Brain Triggers Inflammation And Increasementioning
confidence: 99%
“…Therefore, heparin has direct anti-inflammatory properties [158,159] linked to the binding of proinflammatory factors [160,161]. Heparin has been shown to specifically decrease the number of leukocytes participating in the inflammatory response to any insult occurring within the CNS [162,163]. In fact, UFH is a potent inhibitor of the adhesion molecules such as both leukocytes and endothelial cell selectins [164].…”
Section: Heparin and Sahmentioning
confidence: 99%